What Equivocal Data From Single Case Comparison Studies Reveal About Evidence-Based Practices in Early Childhood Special Education. (June 2016) - Ledford, Jennifer R.; Barton, Erin E.; Hardy, Jessica K.; Elam, Katie; Seabolt, Jordan; Shanks, Meredith; Hemmeter, M. L.; Kaiser, Ann
Although comparison studies are important in early intervention/early childhood special education (EI/ECSE), results of well-designed comparison studies are likely to be unpublished because of undifferentiated or differently differentiated results across participants. The purpose of this article is to highlight the utility of comparison designs in the identification of evidence-based interventions for individual children. We present results from three single case comparative studies analyzing embedded and massed-trial instruction, high- and low-fidelity instruction, and small group versus 1:1 instruction conducted in ECSE settings. All participants learned all targeted behaviors in both instructional conditions and learned no behaviors assigned to control conditions. Results suggest that evidence-based practices are not a "one-size-fits-all" conclusion and that data-based decision making is critical even when empirically supported interventions are used.